ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN - Gunawan, Revika Averamita; Nariman, Augustpaosa (Jurnal Paradigma Akuntansi, 2024)
This study aims to examine the effect of firm growth, firm age, profitability, and liquidity on firm value. This study focuses on manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2018 - 2020 with a total sample of 74 companies from 173 company populations. This research uses purposive sampling method which is a technique for taking samples with certain considerations/criteria. In this study, the data analysis techniques used were classical assumption test, multiple linear analysis, and hypothesis testing. This research shows that firm growth, firm age, and liquidity have no significant and negative effect on firm value. Meanwhile, profitability has a significant and positive effect on firm value.